Quality of Drug in Health Facilities: A Cross-sectional Study - Karki, Khem Bahadur; Dhakal, Neelam; Humagain, Baburam; Pandit, Arpana; Acharya, Trishna; Gyanwali, Pradip (Journal of Nepal Health Research Council, 2021)
Background: Poor quality drugs result minor to detrimental effect on human health. The drug should be of standard quality and should be used appropriately in order to meet its therapeutic efficacy. This study aims to assess the quality of drug in Nepal. Methods: A cross sectional study was conducted in randomly selected 88 health facilities in Nepal from 10th April to 30th June 2016. Selective medicines were collected from both private licensed pharmacies and selected public health facilities. Face to face interview with health facility in-charge of selected health facilities was carried out along with the direct observation of the medicine storage room. The collected medicine samples were dispatched to two laboratories for in-vitro analysis. The labels of the collected medicine were analyzed. The obtained data were entered in Epidata version 3.1, cleaned in Microsoft excel 2007 and analyzed in SPSS version 20.Results: Out of 172 brands, nine brands of medicines were found substandard. Information regarding storage conditions, direction for use and category of the drug were lacking in the label of some brands of medicines. Some selected health facilities were found not meeting major requirements for drug storage: protection from sunlight, moisture, heat, well ventilation and proper sanitation.Conclusions: Few drugs were found to be substandard in Nepalese market from both public and private sectors. Adequate labeling and proper storage condition of medicines in health facilities were lacking.Keywords: Drug quality; private pharmacies; public health facilities; substandard drugs.